Relationship between dietary fats and serum antioxidants with atheromatic index in regular blood donors. (October 2020) - Pritsa, Agathi; Tsamesidis, Ioannis; Samara, Diana; Papadopoulou, Kyriaki S.; Parpori, Maria; Gkinoudis, Argyrios; Lymperaki, Evgenia
Summary: Background & objectives: Nutritional choices, which include dietary fatty acids (FA), vitamins and sugars, have an important significant impact on the development of atheromatic index levels. Controversial opinions exist in the literature regarding the role of different fat types and their association with atheromatic index. We investigated the relationship between dietary intake with different atheromatic index groups of volunteer regular blood donors (rBDs) recognizing them as a healthy population excluding drug and supplements intake and we correlated their values with serum total antioxidant status (sTAS). Material & methods: 150 individuals used in this study were divided in 3 groups according to their atheromatic index (AI = Total cholesterol/HDL) (AI): Group 1 (AI < 3.5) comprised of 50 rBDs, Group 2 (AI 3.5–4.49) of 52 rBDs and Group 3 of 48 rBDs (AI > 4.5). Dietary intake was assessed using the 3 day food recall and the Food Processor, computer program for nutrient analysis. sTAS was measured in all samples and correlated with atheromatic index too. Results: Our study showed that rBDs with low dietary intake of all vitamins, Ω3 fatty acids, trans fatty acids and dietary cholesterol presented an increased atheromatic index. On the other hand rBDs with high dietary intake of saturated fat, total fats, monounsaturated and polyunsaturated fats and sugar showed increased atheromatic index. In addition, groups with the higher atheromatic index presented statistically significant higher total antioxidant status. Trans FA are also positively associated with sTAS and on the other hand dietary cholesterol is negatively associated with sTAS and positively in groups B and C. Conclusions: The results of the present study showed that dietary intake of different types of fatty acids should be used separately as atheromatic index predictors. Moreover, sTAS is correlated with dietary intake of SFA, MUFA, PUFA, Cholesterol, Trans FA and sugar. Finally, the measurement of each fatty acid would be of great value for the screening of lipid metabolism disorders in atheromatic index control.